Open and distance learning during Malaysian Movement Control Order 2020: Reflections from University students / Fadzilah Abdol Razak and Nor Rashidah Paujah @ Ismail - Abdol Razak, Fadzilah; Paujah @ Ismail, Nor Rashidah (Universiti Teknologi MARA, Perak, 2021)
The Coronavirus disease 2019 (COVID-19) outbreak has prompted universities in Malaysia to take a step to implement online teaching and learning in line with the instruction of the Ministry of Higher Education not to conduct face-to-face lectures but to take advantage of Online and Distance Learning (ODL) method starting from April 2020. Since this instruction needs to be implemented immediately, the question arises as to whether students are ready to pursue their studies remotely. Hence, the purpose of this study is to determine the readiness of university students to continue their studies using the ODL method. The study also aims to investigate students' reflection after completing the ODL process and to list the factors that contribute to the student's survival in the ODL courses. This study utilized both qualitative and quantitative methods to analyze the data obtained. Key findings revealed that reflection of students towards the implementation of ODL can be categorized into three main categories which are positive, negative and neutral reflections. Overall, negative reflections given by the students can be categorized into four main issues which are adaptability struggle, unconducive learning environment, lack of readiness for self-directed learning and technical issues. Among the four issues, adaptability struggle is the major concern for students as 55.2% of students remarked the ODL as difficult, hard, tough and stressful especially for a course that involved calculation. The outcomes from the study suggest that many students are still in the process of adapting to the implementation of ODL. Even after experiencing the ODL, 30.3% of the students still prefer the traditional face-to-face learning compared to the ODL method. The lecturers and university administration should motivate students on the implementation of ODL and work to solve the four main issues raised by students if they want this method to be implemented successfully in the future.